2016
DOI: 10.3923/rjmp.2016.55.66
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Ginger (Zingiber officinale) Rhizome and Watermelon (Citrullus lanatus) Seeds in Mitigating Aspartame-Induced Oxidative Stress in Rat Model

Abstract: Aspartame (ASP) consumption has been reported to implicate oxidative stress and antioxidant supplements from plant origin are one of the safest ways of averting their effect in the body. The current study was aimed at ascertaining the ability of aspartame (ASP) to induce oxidative stress in rats as well as assessing the potential of ginger (Zingiber officinale) rhizome and watermelon (Citrullus lanatus) seeds extracts in averting the aspartame induced oxidative stress. This was done using sperm parameters and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…It is also medically used for its immunomodulatory, anti-tumorigenic, anti-inflammatory, antiapoptotic and antioxidant properties (11). In addition, it was found that Zingiber officinale is associated with a beneficial effect on male reproductive functions in rats, which confirmed by other studies on the increased sperm counts, motility, testosterone, and decreased malonhydialdehyde levels (12-16). …”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is also medically used for its immunomodulatory, anti-tumorigenic, anti-inflammatory, antiapoptotic and antioxidant properties (11). In addition, it was found that Zingiber officinale is associated with a beneficial effect on male reproductive functions in rats, which confirmed by other studies on the increased sperm counts, motility, testosterone, and decreased malonhydialdehyde levels (12-16). …”
Section: Introductionsupporting
confidence: 81%
“…Ginger also contains [6]-gingerol, 8-gingerol, 10-gingerol and 12-gingerol, which have similar anti-oxidate properties (27, 31). Animal modeling showed that ginger significantly lowered induced lipid peroxidation and amplified the levels of antioxidant enzymes, quantity and quality of sperm and plus serum glutathione (9, 16, 17, 32). …”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have revealed that long‐term consumption of ASP leads to toxicity in brain, liver, kidney, and immune organs by induction of oxidative stress (OS) 3‐9 . Recently evidences have indicated that ASP could be toxic for male reproductive system so that high dose administration of ASP at long‐periods causes induction of OS in this system 10,11 . Ashok et al reported that long‐term consumption of ASP, even at acceptable daily intake dosage (40 mg/kg body weight) decreases antioxidants and increases lipid peroxidation in testes of rats and also diminishes sperm parameters 12 .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Recently evidences have indicated that ASP could be toxic for male reproductive system so that high dose administration of ASP at long-periods causes induction of OS in this system. 10,11 Ashok et al reported that long-term consumption of ASP, even at acceptable daily intake dosage (40 mg/kg body weight) decreases antioxidants and increases lipid peroxidation in testes of rats and also diminishes sperm parameters. 12 However, the mechanism of ASP induced reproductive toxicity is not clearly demonstrated.…”
mentioning
confidence: 99%
“…Ginger causes a significant decrease in the physical signs of initial dysmenorrhoea (10). Studies indicate that the extract of ginger stimulates menstruation, eliminates the irregularities in the menstruation cycle, increases spermatogenesis and enhances sperm fertility factors (11,12). Furthermore, ginger is used to treat fever, rheumatism, neuronal diseases, gingivitis, tooth pain, asthma and coughing (13).…”
Section: Introductionmentioning
confidence: 99%